Echocardiographic evaluation of complete and incomplete Kawasaki disease in terms of coronary and non coronary cardiac involvement - Sarkar, Uttam Kumar; Chatterjee, Anish; Periwal, Sumit; Basu, Suprit; Dutta, Indranil (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: With increasing incidence of Kawasaki disease and its associated complications, the need of the hour is early diagnosis. Incomplete Kawasaki is often diagnosed late and is frequently associated with morbidities and mortalities. Our study aims to emphasize the importance of echocardiography in detection of incomplete Kawasaki disease. Materials & Methods: A total of 150 children, clinically diagnosed as Kawasaki disease were evaluated echocardiographically and involvement of coronary artery and associated cardiac involvements were studied. Results: Amongst the incomplete Kawasaki disease patients 76% were from extremes of ages and 19.2% of them had coronary involvement. Myocarditis(38.1%) was the commonest non-coronary findings. Conclusion: Atypical Kawasaki disease is more common in extremes of ages and echocardiography helps in detecting atypical disease at the earliest, thus facilitating prompt treatment and reducing complications.